Experimental study of tribological and mechanical properties of aluminum matrix reinforced by Al2O3/CNTs. Issue 7 (3rd July 2019) - Zayed, Ahmed Sh.; Kamel, Bahaa M.; Abdelsadek Osman, Tarek; Elkady, Omayma A.; Ali, Shady
Abstract: In recent years, since the discovery of Nano-additives especially carbon nanotubes (CNTs) and graphene, many interesting articles on composites with CNTs have been studied. CNTs have attracted considerable interest in all fields of science because of its unique characteristics. In this study, aluminum (Al) matrix reinforcement by the different volume fraction of Al2 O3 and CNTs composites have been manufactured by using a powder metallurgy technique. The effects of tribological behaviors, density, hardness, and compression strength behavior of aluminum matrix Nano-composite were investigated before and after Hot Isostatic pressing (HIP). Transmission Electron Microscopy (TEM) and Scanning Electron Microscope (SEM) were employed to check the CNTs and hybrid composites. Results show that the density of nanocomposites decreased by 38% but after HIP, the density decreased by 45%. In addition, the hardness enhanced by 40% but, after HIP the hardness became 67%. On the other side, the compressive strength enhanced by 38% and 60% before and after HIP respectively. The coefficient of friction of nanocomposites are improved by 39%, 48% with HIP and without HIP while the wear rates improved by the addition of Al2 O3 and CNTs at all volume fraction by 20%, but after HIP the enhancement became 45% at all volume concentration.